Interactive Educational Games Support Early Childhood Symbolic Thinking And Digital Learning: Game Edukasi Interaktif Mendukung Berpikir Simbolik Anak Usia Dini Dan Pembelajaran Digital - Fauziyah, Alfi; Habibah⁠, Sulhatul; Munif, Moh. Vito Miftahul (Academia Open, 2026)
General Background The rapid growth of technological devices requires fundamental pedagogical adaptations to accommodate native generations born into modern environments. Specific Background Although Miftahul Ulum Kindergarten possesses advanced flat panel facilities, current pedagogical practices remain dominated by conventional methods and passive video presentations. Knowledge Gap There is a lack of optimal technology utilization caused by limited educator competence in integrating sophisticated features, leaving young learners struggling to grasp abstract number and letter representations. Aims This study investigates the application of play-based visual media to develop cognitive capabilities among kindergarten students. Results Utilizing a descriptive qualitative approach with observation and interviews, findings reveal that applying specialized play applications significantly increases student enthusiasm, active involvement, and concentration. Furthermore, these application-based activities successfully help students recognize and understand abstract alphabetical and numerical characters. Novelty This research demonstrates that transforming passive screen time into responsive multimedia play directly stimulates executive functions and short-term memory retention for abstract characters in kindergarten settings. Implications Sustainable curriculum integration requires continuous professional development to upgrade technological competence, alongside supportive institutional policies for multimedia innovation. Highlights Utilizing specific play applications transforms passive screen viewing into active student participation. Visual and auditory activities directly advance young learners' ability to recognize numbers. Optimizing technological facilities strictly requires continuous professional development and competence training for teachers. Keywords Interactive Educational Games; Symbolic Thinking; Early Childhood; Digital Learning; Teacher Competence